1997
DOI: 10.2134/jeq1997.00472425002600030013x
|View full text |Cite
|
Sign up to set email alerts
|

Native Plant Productivity and Litter Decomposition in Reclamation of Taconite Iron Ore Tailing

Abstract: Aboveground production and shoot and root litter decomposition rates were measured in amended coarse taconite tailing plots over the second and third growing seasons of a 3‐yr study. Plots were seeded with a mixture of native prairie species that included Andropogon gerardii Vitm., Schizachyrium scoparium (Michx.) Nash, Elymus canadensis L., Bromus kalmii Gray, and Lespedeza capitata Michx. Reclamation treatments included inoculation with indigenous mycorrhizal fungi, three rates of fertilizer, and three rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A key to long-term reclamation success lies in understanding how the reclaimed ecosystem will function through time. Noyd et al (1997) found that as well as increasing plant biomass production, yard waste compost addition (44.8 Mg ha…”
Section: From Larney Et Al (2003a)mentioning
confidence: 99%
“…A key to long-term reclamation success lies in understanding how the reclaimed ecosystem will function through time. Noyd et al (1997) found that as well as increasing plant biomass production, yard waste compost addition (44.8 Mg ha…”
Section: From Larney Et Al (2003a)mentioning
confidence: 99%